Peran Psikologis Orang Tua dalam Pembentukan Kesadaran Pendidikan Anak: Kajian Literatur - Aida Rumaratu; Komariyah Komariyah; Maya Agisty; Riska Latifatul Husna (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2026)
Educational awareness is a psychological construct formed through the quality of emotional interactions within the family environment, serving as the basis for learning orientation. This study aims to explore the psychological role of parents in shaping children's educational awareness and its implications for educational continuity to mitigate the risk of school dropout. Using a qualitative approach with a literature review design, this study applies content analysis to various reputable scientific sources to critically synthesize internal psychological mechanisms within the family. Findings indicate that parental psychological support including empathy, emotional validation, and supportive communication significantly builds intrinsic motivation by fulfilling children's needs for autonomy and competence. This mechanism functions as a vital protective factor that strengthens children's resilience against academic pressures and structural economic constraints. The study concludes that the psychological presence of parents is a fundamental foundation that transforms children's perception of education from a mere formal obligation into a need for continuous self development. This study suggests the urgency of developing psychologically based parenting interventions and conducting longitudinal studies to strengthen preventive strategies in national education policy.